VD_FINDINFO AP / 2010 / 20 vom 27. August 2009 - VD Tribunal cantonal (2009)
INJURE, SURSIS À L'EXÉCUTION DE LA PEINE | 177 al. 1 CP, 177 CP, 42 CP, 47 CP, 411 CPP, 411 let. g CPP, 411 let. h CPP, 411 let. i CPP, 417 CPP, 447 CPP